Fluoroboro Bridged Cyclopean-Type Macrocyclic Co(II), Ni(II) and Cu(II) Complexes - Rai, H.C.; Sinha, Sushma; Rai, B.K. (Asian Journal of Chemistry, 2010)
Diacetylmonohydrazonemonoxime (Fig. I) reacts with formaldehyde, glyoxal and diacetyl to yield a group of ligands (Figs. 2-3) which in turn react with metal salt to give complexes as shown in Figs. 4-5. These complexes react with boron trifluoride in butanol medium to give fluoroboro-bridged macrocyclic complexes as shown in Figs. 6-8 respectively. Characterization has been done on the basis of elemental analyses, IR and electronic spectral studies as well as electrochemical study.